Not just an adhesion molecule : LFA-1 contact tunes the T lymphocyte program - Verma, Navin Kumar (2019)
The αLβ2 integrin LFA-1 is known to play a key role in T lymphocyte migration, which is necessary to mount a local immune response, and is also the main driver of autoimmune diseases. This migration-triggering signaling process in T cells is tightly regulated to permit an immune response that is appropriate to the local trigger, as well as to prevent deleterious tissue-damaging bystander effects. Emerging evidence shows that, in addition to prompting a diverse range of downstream signaling cascades, LFA-1 stimulation in T lymphocytes modulates gene-transcription programs, including genetic signatures of TGF-β and Notch pathways, with multifactorial biological outcomes. This review highlights recent findings and discusses molecular mechanisms by which LFA-1 signaling influence T lymphocyte differentiation into the effector subsets Th1, Th17, and induced regulatory T cells. We argue that LFA-1 contact with a cognate ligand, such as ICAM-1, independent of the immune synapse activates a late divergence in T cells’ effector phenotypes, hence fine-tuning their functioning.